Atypical Carcinoid Tumor of the Lung: A Surveillance, Epidemiology, and End Results Database Analysis. Issue 3 (March 2015) - Steuer, Conor E.; Behera, Madhusmita; Kim, Sungjin; Chen, Zhengjia; Saba, Nabil F.; Pillai, Rathi N.; Owonikoko, Taofeek K.; Khuri, Fadlo R.; Ramalingam, Suresh S.
Abstract : Background: Atypical carcinoid (AC) of the lung is a rare form of thoracic malignancy. The limited knowledge of its biology and outcome stems largely from small, single institution experiences. We analyzed the Surveillance, Epidemiology, and End Results database (SEER) to better understand the clinical characteristics of this disease. Methods: Demographic, treatment, and outcome data on all patients with pulmonary AC were obtained from the SEER database with 18 reporting sites from 1973 to 2010 using SEER*Stat 8.1.2. Statistical analysis was performed using SAS 9.3 (SAS Institute, Inc., Cary, NC). Results: There were 947, 463 patients diagnosed with lung and bronchus tumors in the SEER database, of which 441 had AC (0.05%). Median age of AC patients was 65 years; 69% were women and 87% of white ethnicity. Metastatic disease was present in 20% of patients at diagnosis. In terms of treatment, 78% of patients underwent resection and 12.5% received radiation. The overall 1-year and 3-year survival rates were 86% and 67%, respectively. The 3-year survival rates for distant (M1), regional (lymph node involvement), and localized (lung only) disease were 26% (13 of 50), 69% (50 of 72), and 85% (99 of 116), respectively. On univariate analysis, patients treated with surgery had reduced risk of death (hazard ratio, HR 0.19; p < 0.001), whereas radiation treatment was associated with increased risk of death (HR 2.45; p < 0.001). Conclusions: AC accounted for less than 1% of all lung cancers diagnosed and was more frequent in women. The best outcomes were observed with surgical resection for localized disease.